Food product certification in Ukraine as the leading direction in an international dimension - Ovsiannikova, Valeria (My University, 2014)
The modern food processing industry in Ukraine is developing rapidly, but there are number of problematic issues that will facilitate the entry of competitive Ukrainian products into the international market.
Keywords: food product; certification; international dimension; харчовий продукт; сертифікація; міжнародний аспект; пищевой продукт; сертификация; международный аспект